Optimal design of a district cooling grid: structure, technology integration, and operation. Issue 1 (2nd January 2019) - Al-Noaimi, Fadi; Khir, Reem; Haouari, Mohamed
ABSTRACT: The concept of a district cooling grid that allows the integration of several cooling technologies with different availability and supply patterns is introduced. An integrated multi-period optimization model for a district cooling grid configuration is developed. An approximate decomposition strategy is proposed to aid in the efficient design of large grids. Results of extensive computational study are provided that demonstrate the solvability of the developed model to optimality and the effectiveness of the proposed decomposition strategy as a viable solution approach.